Maternal Nutritional Empowerment Through “Isi Piringku” Education: Longitudinal Analysis Of Stunting Prevention and Life-Cycle Nutritiona Outcomes (2018-2022 Cohort Study) - Basit, Abdul; Arisanty, Deasy (Science Tech Group, 2025)
This study aimed to develop and evaluate an empowerment model for pregnant women using